Stolica Apostolska wobec Państwa Izrael w okresie wojny sześciodniowej - Ignatowski, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2023)
For many Jewish communities involved in the dialogue with Christian Churches it is the most important question to be discussed with their partners: the sources of the modern anti-Semitism and the safety of the State of Israel. That is why they do not look with sympathy at Paul VI pilgrimage to the Holy Land (4 – 6 Jan. 1964). The Pope did not visit the Yad Vashem Institute then, neither did he mention the name of the Jewish state in any of his speeches. However, an analysis of the Pope’s official addresses of the Six Days War period allows to adopt a more positive view of the Pope’s attitudes towards the state of Israel. The Pope demanded then not only the free access to the Holy Places but also the recognition of the State of Israel by the Arab states.